Implementasi Data Mining untuk Manajemen Bantuan Sosial Menggunakan Algoritma K-Means - Ali Ikhwan; Nuri Aslami ((JurTI) Jurnal Teknologi Informasi, 2020)
Abstract- Every sub-district in North Sumatra Province can administer aid funds, one of which can provide priority community assistance to low-income families who are part of the Hope Family Program (PKH). The level of data accuracy must support the regional government's good intentions in alleviating poverty through the family hope program (PKH) for low-income families. There are complexities in processing data so far, that is, determining the poor population who are the top priority for receiving assistance among the many data of the poor in Medan Tembung sub-district; there are complexities in processing data so far, that is, determining the poor population who are the top priority for receiving assistance among the many data of the poor in Medan Tembung sub-district; there are complexities in processing data so far, that is, determining the poor population who are the top priority The difficulty arises as a result of the vast number of disadvantaged people in the sub-district head, who must take into account factors such as welfare status, status, and the number of people in a household. By observing the problem above data mining using the clustering process, very appropriate to be used to generate priority community awareness among hundreds of poor people in Medan Tembung sub-district, the importance of each of these parameters becomes a benchmark for selecting the population that is a top priority to receive assistance from the family hope program (PKH) for low-income families.Keywords  -   Data Mining, Cluster Method, family hope program, Knowledge Abstrak - Setiap kecamatan di Provinsi Sumatera Utara dapat mengelola dana bantuan, salah satunya dapat memberikan prioritas bantuan masyarakat kepada keluarga berpenghasilan rendah yang tergabung dalam Program Keluarga Harapan (PKH). Tingkat akurasi data harus mendukung niat baik pemerintah daerah dalam mengentaskan kemiskinan melalui program Keluarga Harapan (PKH) bagi keluarga berpenghasilan rendah. Terdapat kerumitan dalam pengolahan data selama ini yaitu menentukan penduduk miskin yang menjadi prioritas utama penerima bantuan di antara sekian banyak data penduduk miskin di Kecamatan Medan Tembung; terdapat kerumitan dalam pengolahan data selama ini yaitu menentukan penduduk miskin yang menjadi prioritas utama penerima bantuan di antara sekian banyak data penduduk miskin di Kecamatan Medan Tembung; ada kerumitan dalam pengolahan data selama ini yaitu menentukan penduduk miskin yang menjadi prioritas utama Kesulitan itu muncul akibat banyaknya jumlah penduduk miskin di camat, yang harus mempertimbangkan faktor-faktor seperti kesejahteraan status, status, dan jumlah orang dalam suatu rumah tangga. Dengan mencermati permasalahan di atas data mining menggunakan proses clustering, sangat tepat digunakan untuk membangkitkan prioritas kesadaran masyarakat di antara ratusan masyarakat miskin di Kecamatan Medan Tembung, pentingnya masing-masing parameter tersebut menjadi tolak ukur untuk memilih populasi yang akan dipilih. menjadi prioritas utama untuk menerima bantuan Program Keluarga Harapan (PKH) bagi keluarga berpenghasilan rendah. Kata Kunci - Data Mining, Metode Cluster, Program Keluarga Harapan, Pengetahuan.